Program Pencegahan Penularan COVID-19 pada Komunitas Ibu Rumah Tangga dengan HIV di Surabaya - Hanna Tabita Hasianna Silitonga; Etha Rambung; Romauli Nainggolan; Gusto Benyamin Messakh; Keith Justine Thiotansen (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
Everyone was affected by COVID-19 pandemic, including housewives with HIV joined in Bu'Daya community. In management of COVID-19, patient's comorbid history was important because these patients could aggravate the condition of COVID-19. HIV was a chronic disease related to the immune system. Therefore, it was important for people with HIV to prevent infection of COVID-19. The problem faced by this community regarding COVID-19 was knowledge and attitudes of community members was not known yet. Therefore, efforts were needed to find out and improve understanding of COVID-19. The solution offered to this community was training and assistance regarding the prevention of COVID-19 through the "We Are Empowered, We Prevent Covid-19 Transmission" Program. This program was part of a series of “We Are Empowered” programs, a service program of the Empower Woman with HIV, in Surabaya. The aim of this program was to increase knowledge and attitudes of the participants towards preventing the transmission of COVID-19. The implementation method was by community education, training and community assistance. The results obtained from this community service were the increased knowledge and attitudes of the participants regarding the behavior of preventing the transmission of COVID-19 which could be seen from the pre and post-test results. DOI: https://doi.org/10.26905/abdimas.v5i3.4844